Digital Transformation Strategies of Rural Banks in Depok in Response to Fintech Disruption - Ahmad Firdaus; Meirna Milisani; Prihatina Jati (Annals of Human Resource Management Research, 2026)
Purpose: This study aims to investigate the digital transformation strategies of Rural Banks (BPR) in Depok City in response to the disruption of fintech and digital banking, with a particular focus on the roles of organizational readiness, digital service adoption, technological infrastructure, and regulatory compliance in shaping financial performance. Research Methodology: A quantitative approach was employed, utilizing survey data from 19 BPRs in Depok City and secondary financial reports from 2022 to 2024. Data were analyzed using statistical techniques to assess the relationships between organizational and technological factors and financial performance outcomes. Results: The findings reveal that human resource readiness and digital service adoption significantly enhance the financial performance of BPRs. In contrast, technological infrastructure and regulatory compliance have relatively weaker impacts. These results underscore that successful digital transformation requires not only technological investment but also a strong emphasis on organizational culture and continuous employee upskilling. Conclusions: Digital transformation in BPRs cannot be achieved solely through infrastructure upgrades; it necessitates alignment between human resource capabilities, innovation in service delivery, and governance structures that build trust. Limitations: The study is limited to BPRs within Depok City, with a sample size of 19 institutions, which may restrict the generalizability of findings to other regions or larger financial institutions. Contributions: This research enriches the literature on digital transformation in smaller financial institutions and providing practical insights.